A study to assess the knowledge of final year B.Sc. Nursing students regarding genetics and its importance in nursing care at selected nursing colleges of Anand and Kheda district of Gujarat state - Pandya, Arpan; Patidar, Jayesh; Barot, Ravi (International Journal of Nursing Research, 2023)
Aim: The aim of this study was to assess the knowledge of students regarding genetics and its importance in nursing care. Materials and methods: The research tools were prepared after discussion and validation from experts in nursing field and genetics. The tool was prepared in two segments. The first segment was consist of demographic variables of students like the age of participants, marital status, nursing experience in genetic disease, attended the specialized program on genetics and its use in nursing and gender of participants. Results: The results of the study revealed that the majority of the participant is having the average knowledge regarding the genetics and its importance in nursing care. The study also revealed that students need to emphasize on knowledge of genetics. Conclusion: The study concluded that knowledge of genetics among nursing students will promote better Nursing services